Herbal and nano-based herbal medicine: New insights into their therapeutic aspects against periodontitis - Fatemeh Rezaei-Tazangi; Armita Forutan Mirhosseini; Amirhossein Fathi; Hossein Roghani-Shahraki; Reza Arefnezhad; Fateme Vasei (Mashhad University of Medical Sciences, 2024)
Objective: Periodontitis is a type of prevalent chronicinflammatory disorder resulting in a failure in the function oftissues supporting the tooth, like gingiva, alveolar bone, andperiodontal ligament. Although antibiotic therapy is a commontherapy for periodontitis cases, this approach can cause someadverse effects in these patients. Thus, finding an effectivecurative option with low side effects is still a puzzle.Materials and Methods: This narrative review was conducted onthe effects of herbal and nano-based herbal medicine againstperiodontitis by searching different databases such as GoogleScholar, PubMed, Scopus, Web of Science, Science Direct, andScientific Information Databases.Results: According to published studies, some popular herbalformulations, such as Aloe vera, curcumin, Melaleuca alternifolia,and Scutellaria baicalensis Georgi, can be effective in periodontitistreatment. However, these herbal products may be accompaniedby some pharmacological limitations, such as poor bioavailability,instability, and weak water solubility. On the other hand,harnessing nano-based herbal formulations can elevate thebioavailability, diminish toxicity, and omit repeated administrationof drugs.Conclusion: Herbal and nano-based herbal products can create agood chance to treat periodontitis efficiently.